Tabakdosen für Seefahrer. Hollands auf Zielgruppen ausgerichtetes Verpackungsdesign im 18. Jahrhundert - Ellmers, Detlev (Deutsches Schiffahrtsarchiv, 2020)
On the basis of the few tobacco containers in the German Maritime Museum and through comparison with several receptacles from other collections, it was possible to determine how, in the fourth quarter of the seventeenth century, a Netherlandish manufacturer made the transition from the manufacture of wooden splint boxes to the serial production of brass tobacco tins. As a way of deliberately influencing their distribution, he marketed the boxes for specific previously defined target groups by decorating them with engraved pictorial representations. The most elaborately designed specimens were intended to appeal to courtly cavaliers who, however, soon came to prefer more sophisticated alternatives. The sailors, helmsmen, and gunners on military and large merchant vessels each made up a target group of their own, and were lured to purchase boxes with depictions related specifically to themselves, as was also the case with small-time maritime merchants. When one of these persons purchased a container of this sort, he came to possess not only a practical item for everyday use but also - for the first time in a private context - a prestige object of his specific class. In accordance with guild customs, the members ranking below the masters and skippers otherwise owned no private prestige objects, but only the objects belonging jointly to their groups. The owners of serially produced brass tins were clearly distinguished from the wealthy merchants, the skippers of voyages to the East Indies, and even the naval officers on warships through the production of individual tobacco receptacles from more precious materials and with more individualized pictorial representations to indicate their elevated standing. With its handful of serially and individually produced tobacco containers, the German Maritime Museum offers an exemplary overview of the entire spectrum of these prestige objects designed for the seafarers of the eighteenth century.
Keywords: Seefahrer; Tabak; Tabaksdose

Tabak. Medizin, Laster, Genuss - Käss, Alexandra (Augenlust? Niederländische Stillleben im Detail. Ausstellungskatalog LVR-LandesMuseum Bonn, 22.09.2022–19.02.2023, 2022)
Keywords: Medizin; Stillleben; Tabak; Tabaksdose